Are we a step forward with targeted agents in resolving the enigma of mantle cell lymphoma? - Petković, Ivan; Pejčić, Ivica; Vrbić, Svetislav (Contemporary Oncology/Współczesna Onkologia, 2014)
Mantle cell lymphoma has been recognized as a distinct entity from the other non-Hodgkin lymphomas in middle 1990’s. It carries a worst prognosis among all mature B-cell malignancies. Cyclin D1 and recently SOX11 are the hallmarks for this disease. Even if it is highly responsive to induction treatment, it remains incurable, since it inevitably relapses. Highly aggressive approaches with stem cell transplantation can shift the survival curve for a bit, but even so the overall survival is not significantly improved in most of the cases. Small portion of patients with this heterogeneous disease have an indolent course with long-term survival. Conventional immunochemotherapy has reached its maximal possibilities, so novel target agents are absolutely warranted. The large number of ongoing early phase trials demonstrated promising results, especially emphasizing agents that target B-cell receptor. They are mostly investigated in relapsed/refractory disease, while front-line approaches with those agents need to be explored in future times.